Implementation of Kediri City Government Policy in Developing MSMEs Post the Covid 19 Pandemic - Diana Ambarwati; Imam Mukhlis (Cita konsultindo, 2023)
The sharp decrease in economic growth in 2020 indicates that a number of corporate actors were having issues at the time. It is believed that the Covid-19 epidemic, which began on February 29, 2020, is to blame for this issue. This is what prompted the Kediri City government to develop a plan for resuming economic growth in the form of laws. This study intends to identify the Kediri City government's policy framework for MSMEs development following the Covid-19 pandemic. This study employs qualitative methodologies, that involve gathering data from library literature studies by gathering data from journals, reports on official government websites, by collecting data from photos of activities and videos on social media related to research and observations, and interviews with 3 (three) informants who are MSMEs under the supervision of the Cooperative and MSME Office of Kediri City. Data analysis this research use Nvivo 12. The findings of this study demonstrate that the Kediri City Government's manner of policy implementation significantly results in a digitalization program that appeals to all parties, notably MSMEs.